Una entrevista con el Dr. Vic Sidel / An interview with Dr. Vic Sidel - Capps, Linnea; Smith, Clyde Lanford (Lanny) (Social Medicine, 2013)
Una entrevista con el Dr. Vic Sidel An interview with Dr. Vic Sidel